Dilemmas of Distrust: Conspiracy Beliefs, Elite Rhetoric, and Motivated Reasoning. (December 2022) - Radnitz, Scott
Conspiracy theories are playing an increasingly prominent role worldwide in both political rhetoric and popular belief. Previous research has emphasized the individual-level factors behind conspiracy belief but paid less attention to the role of elite framing, while focusing mostly on domestic political contexts. This study assesses the relative weight of official conspiracy claims and motivated biases in producing conspiracy beliefs, in two countries where identities other than partisanship are salient: Georgia and Kazakhstan. I report the results of a survey experiment that depicts a possible conspiracy and varies the content of official claims and relevant contextual details. The results show that motivated reasoning stemming from state-level geopolitical identities is strongly associated with higher conspiracy belief, whereas official claims have little effect on people's perceptions of conspiracy. Respondents who exhibit higher conspiracy ideation are more likely to perceive a conspiracy but do not weight motivated biases or official claims differently from people with lower conspiratorial predispositions. The findings indicate the importance of (geopolitical) identities in shaping conspiracy beliefs and highlight some of the constraints facing elites who seek to benefit from the use of conspiracy claims.